Pengaruh Pengembangan Produk dan Promosi terhadap Peningkatan Volume Penjualan Pada Perusahaan Konveksi “Mentari“ di Klaten, Indonesia - Toni Prastowohadi (Asosiasi Ahli Administrasi Indonesia, 2020)
Every company is required to continue to improve the quality of its products by gradually improving its marketing strategies so that the products produced are known to the wider community, including distribution so that they reach consumers easily. This study intends to examine the effect of product development and sales promotion on increasing sales volume. The research method used is quantitative data and uses multiple regression analysis. The results showed that product development and promotion affected the sales volume of convection products. However, an increase in product development costs contributes more to an increase in sales volume than an increase in promotional costs. Competition in the field of convection faces many challenges both internally and externally, but if we are open to change and use the right strategy, the company will be able to survive and have a competitive edge for business sustainability in the future.